2014
DOI: 10.5001/omj.2014.77
|View full text |Cite
|
Sign up to set email alerts
|

Malignant Multivessel Coronary Spasm Complicated by Myocardial Infarction, Transient Complete Heart Block, Ventricular Fibrillation, Cardiogenic Shock and Ischemic Stroke

Abstract: Multivessel coronary spasm resulting to cardiogenic shock and malignant ventricular arrhythmias though rare has been reported in the literature. The disease seems to be more prevalent in Asians. There have been isolated reports of coronary spasm in patients with reactive airway disease. We report the first case of spontaneous multivessel spasm in a male patient with bronchial asthma of Arab ethnicity resulting in acute myocardial infarction complicated by cardiogenic shock, recurrent ventricular arrhythmias, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Intracoronary nitroglycerin (ICN) should not be given to hemodynamicaly unstable patients, as our patient was in shock with norepinephrine support and dramatic response of ICN in relieve vasospasm and improvement of hemodynamics, it suggests that local response of ICN is more potent than the systemic response of norepinephrine, it is also consistent with case report of Thomson v et al 5 In summary, diagnosing CAS is really important but challenging to prevent complication like MI, arrhythmias and sudden cardiac death from occurring. At the same time we should also keep in mind Malignant multi-vessel coronary spasm as a cause if patient present with its rare complication as MI and shock.…”
Section: Discussionsupporting
confidence: 88%
“…Intracoronary nitroglycerin (ICN) should not be given to hemodynamicaly unstable patients, as our patient was in shock with norepinephrine support and dramatic response of ICN in relieve vasospasm and improvement of hemodynamics, it suggests that local response of ICN is more potent than the systemic response of norepinephrine, it is also consistent with case report of Thomson v et al 5 In summary, diagnosing CAS is really important but challenging to prevent complication like MI, arrhythmias and sudden cardiac death from occurring. At the same time we should also keep in mind Malignant multi-vessel coronary spasm as a cause if patient present with its rare complication as MI and shock.…”
Section: Discussionsupporting
confidence: 88%
“…Vasospastic angina (VA) is a type of unstable angina with coronary artery spasm (CAS) as the main pathogenesis. Studies have shown that multivessel CAS can cause sudden cardiac arrest or fatal ventricular arrhythmias [1,2]. VA is implicated in various heart diseases including acute coronary syndrome, and fatal arrhythmic events [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…In rare cases, multivessel CAS can lead to life-threatening ventricular arrhythmias or sudden cardiac arrest. 1 , 2 Although invasive coronary angiography (CAG) with provocation testing is the diagnostic gold standard in current VSA guidelines, 3 it may potentially lead to ergonovine-related life-threatening complications, 4 and it is also difficult to observe both the left and right coronary artery simultaneously. As a non-invasive method of cardiac imaging, to avoid these complications is difficult with coronary computed tomography angiography (CCTA), but it can reduce vascular access site complications, while provide additional information.…”
Section: Introductionmentioning
confidence: 99%